2020
DOI: 10.1055/s-0040-1712101
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Ventilation and High-Flow Nasal Therapy Administration in Chronic Obstructive Pulmonary Disease Exacerbations

Abstract: Noninvasive ventilation (NIV) is considered to be the standard of care for the management of acute hypercapnic respiratory failure in patients with chronic obstructive pulmonary disease exacerbation. It can be delivered safely in any dedicated setting, from emergency rooms to high dependency or intensive care units and wards. NIV helps improving dyspnea and gas exchange, reduces the need for endotracheal intubation, and morbidity and mortality rates. It is therefore recognized as the gold standard in this cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 95 publications
0
2
0
1
Order By: Relevance
“…Im Wesentlichen wird der intrinsische PEEPi durch Einsatz des externen PEEP antagonisiert und durch die zusätzliche maschinelle Druckunterstützung die diaphragmale Atemarbeit reduziert 13 14 15 . Zusätzlich senkt der externe PEEP die zum Triggern der Druckunterstützung erforderliche inspiratorische Atemarbeit des Patienten 16 .…”
Section: Hyperkapnische Ariunclassified
“…Im Wesentlichen wird der intrinsische PEEPi durch Einsatz des externen PEEP antagonisiert und durch die zusätzliche maschinelle Druckunterstützung die diaphragmale Atemarbeit reduziert 13 14 15 . Zusätzlich senkt der externe PEEP die zum Triggern der Druckunterstützung erforderliche inspiratorische Atemarbeit des Patienten 16 .…”
Section: Hyperkapnische Ariunclassified
“…Cortegiani et al 14 used non-invasive ventilation and HFNC to treat patients with COPD and acute hypercapnia exacerbation, and the results confirmed that the effects of both methods were equivalent. Research by Miquel Ferrer et al 15 has also confirmed that HFNC has high application value in patients with COPD, can improve gas exchange, alleviate breathing difficulties, and has important significance in reducing disease mortality and tracheal intubation rates. Our findings are consistent with the above studies.…”
Section: Discussionmentioning
confidence: 93%
“…Based on those potential mechanisms above, it is reasonable to use HFNC in AECOPD patients [ 1 ], but its efficacy and safety in such patients are not clear [ 16 ]. In order to unite the advantages of NIV and HFNC, we designed this trial to evaluate the effect of HFNC with sequential NIV versus NIV alone on patients with mild-to-moderate AECOPD.…”
Section: Introductionmentioning
confidence: 99%